Digital Mathematics Learning and Its Challenges: A Systematic Literature Review - Ni Wayan Suardiati Putri; Kadek Suryati; Evi Dwi Krisna (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
The development of digital technology has driven changes in mathematics learning in higher education, while also presenting new opportunities and challenges. This study aims to examine the implementation of digital mathematics learning and its accompanying challenges through the Systematic Literature Review (SLR) method with reference to the PRISMA guidelines. A total of 20 articles that met the inclusion criteria were analyzed qualitatively using thematic synthesis. The results of the study indicate that digital mathematics learning in higher education utilizes various technologies, such as Learning Management Systems (LMS), interactive media, learning videos, digital simulations, and blended and hybrid learning models. Digital mathematics learning has a positive impact on students' conceptual understanding, motivation, independence, and digital literacy, but its effectiveness is greatly influenced by the learning design and pedagogical strategies of lecturers. The main challenges identified include limited interaction, digital literacy gaps, technological readiness, and infrastructure and pedagogical constraints. Therefore, the integration of technology in mathematics learning needs to be supported by strengthening lecturer competencies and appropriate learning planning for effective and sustainable implementation.